Price and Marketing Strategy in Tourism Contexts: A preliminary study to mitigating seasonality - Barros, César (2019)
Tourism, as an area of study, has expanded its scope, reflecting an increasing recognition in the academic community paralleled by the application of interdisciplinary concepts and methods. In this context, seasonality has long been viewed as one of the most unique and worrisome facets of the tourism industry. It can be defined as a cyclical pattern that more or less repeats itself each year. In this context, the element of marketing-mix that has been most impervious to sharing power with consumers is precisely the price. Participative pricing mechanisms have been used by for-profit entities for quite some time, and some of the most innovative participative pricing strategies have been applied in different industries throughout the past decades. The studies show the importance of investigating more about the price and phenomenon of seasonality in tourism contexts. Such is the case of Name Your Own Price and Pay What You Want. This preliminary research intends to provide evidence that identity and self-image concerns are potentially very important (in specific tourism contexts). Three field experiments will involve PWYW pricing demonstrate that companies can sustain profitability with payments that rely entirely on social preferences in Portuguese hospitality and tourism (i.e. Theme Park Experiment (Radical Tourism); Tour Boat Experiment (Douro River) and Religious Tourism (Fátima)). This study is an exploratory research based on a quantitative approach with the increasing competition among tourist and specific tourism contexts. At the end of the study, some limitations will be presented and lines of research will be outlined for the future.